Análisis de la potencialidad del circuito agroturístico en la Hacienda Clementina cantón Babahoyo - Valencia Guayaquil, Yordan Marco (2020)
The objective of this case study is to analyze the potential of an Agrotourism circuit of the Clementina farm, Babahoyo canton, with the aim of carrying out Agrotourism activities in the natural landscapes of the same, so that new sources of work are generated in the sector for the community and the owners. For the development of this research, the field methodology was used to know and examine the natural resources and the surroundings of the farm, it was also discovered the causes that do not allow tourism development to implement a circuit in the natural landscapes of the farm. It was determined that in the Clementina farm, within the necessary elements of the circuit, it is implemented in it, starting from a route (entry - exit) in addition to aspects of general reviews of basic services such as: energy, drinking water, telephone signal and internet deficient, to satisfy the different needs of tourists when they visit the sector. These factors do not allow the tourist development of the Clementina farm. As items, the sector and the owners must be associated, to potentiate and strengthen the tourist demand through training of guides (natives - professionals), and adapt the tourist resources to carry out an Agrotourism circuit